2 BACKGROUNDS OF SELECTIVE SERVICE: MILITARY OBLIGATION: THE AMERICAN TRADITION, Part 6 (Massachusetts), at 26, 31 (1645). (Arthur Vollmer ed., 1947) - (:unkn) unknown (General Publisher, 1645)
Ordered all youth aged ten to sixteen shall be instructed in the exercise of arms like small guns, half-pikes, bows and arrows.
--
Keywords: TRAINING